Gambaran Pengetahuan tentang Pencegahan Kanker Serviks dengan Vaksin HPV pada Mahasiswi S1 Keperawatan di Daerah Istimewa Yogyakarta - Rafita Ramdan Nurul Fuadah; Wenny Artanty Nisman; Wiwin Lismidiati (PSIK FKKMK UGM, 2019)
Background: Lack of knowledge is one of the factors that may lead to an increase risk of cervical cancer. Lack of the knowledge can also affect the attitude of a health worker to the patient. Therefore, it is important to find out the knowledge about cervical cancer prevention with HPV vaccine among undergraduate nursing students. Moreover, the research around this topic is underexplored.Objective: To know the level of knowledge of cervical cancer prevention with HPV vaccine among undergraduate nursing students.Method: This research is a descriptive qualitative research. The sample taken consists of 95 female students from two universities, recruited by simple random sampling and consecutive sampling. The instrument used in this study was a cervical cancer prevention knowledge questionnaire with HPV vaccine compiled by researchers. Validity test result was r >0,174 and reliability test result was 0,460. The data analisys was conducted through univariat technique.Result: The results show that total of 49 (52%) respondents have general knowledge regarding cervical cancer and the HPV vaccine. For details per domain, most respondents had good knowledge of cervical cancer risk factors (94,7%), signs and symptoms of cervical cancer (56,8%), and causes of cervical cancer (51,6%), and HPV vaccine administration (44,2%). While in the domain of understanding and administering vaccines the majority of respondents still have less knowledge (81,1% and 55,8%).Conclusion: Nursing undergraduate students have good knowledge about cervical cancer prevention with HPV vaccine, but knowledge on some indicators is still lacking. Knowledge about cervical cancer prevention with HPV vaccine in nursing undergraduate students still needs to be improved especially in indicators of understanding cervical cancer, causes, signs and symptoms of cervical cancer and the administration of HPV vaccine. ABSTRAKLatar Belakang: Rendahnya pengetahuan merupakan salah satu faktor penyebab tingginya kejadian kanker serviks. Pengetahuan yang rendah juga dapat memengaruhi sikap seorang tenaga kesehatan terhadap pasien. Sementara, penelitian terkait tingkat pengetahuan pencegahan kanker serviks dengan vaksin HPV pada mahasiswi keperawatan, masih sedikit. Oleh karena itu penelitian terkait pengetahuan pencegahan kanker serviks dengan vaksin HPV pada mahasiswi keperawatan perlu dilakukan.Tujuan: Mengetahui gambaran pengetahuan mahasiswi S1 Keperawatan tentang pencegahan kanker serviks dengan vaksin HPV.Metode: Jenis penelitian ini adalah deskriptif kuantitatif. Responden penelitian adalah mahasiswi di 2 universitas. Sampel dalam penelitian ini berjumlah 95 mahasiswi dengan teknik pengambilan sampel simple random sampling dan consecutive sampling. Instrumen yang digunakan dalam penelitian ini adalah kuesioner pengetahuan yang disusun oleh peneliti dengan hasil uji validitas (r > 0,174) dan reliabilitas sebesar 0,460. Analisis data dilakukan secara univariat.Hasil: Sebanyak 49 (52%) responden mempunyai pengetahuan baik. Sebagian besar responden memiliki pengetahuan baik terkait faktor risiko kanker serviks (94,7%), penyebab kanker serviks (51,6%), tanda dan gejala kanker serviks (56,8%) dan pemberian vaksin HPV (44,2%). Namun, responden masih memiliki pengetahuan yang kurang tentang pengertian kanker serviks dan pemberian vaksin HPV (81,1 % dan 55,8%).Kesimpulan: Secara umum mahasiswi S1 keperawatan memiliki pengetahuan baik mengenai pencegahan kanker serviks dengan vaksin HPV, namun pada beberapa indikator pengetahuan mahasiswa masih kurang. Pengetahuan tentang pencegahan kanker serviks dengan vaksin HPV pada mahasiswi S1 Keperawatan masih perlu ditingkatkan terutama pada indikator pengertian kanker serviks, penyebab, tanda dan gejala kanker serviks dan pemberian vaksin HPV.